PENYUSUNAN TES PENYESUAIAN DIRI UNTUK SURVIVOR KANKER PAYUDARA - Hanifah Hanifah; Eka Rasyid Deatri; Nesia Natalie; Nelly D. P.; Nanda Rosalia (MANASA, 2012)
Cancer is one of the deadliest disease in Indonesia. The most common cancer in Indonesia is breast cancer. Breast cancer is more dominated by women rather than men, where the ratio is 9 to 1. Women that are diagnose with breast cancer and had surgery but also undergone treatment for five years or more are called the breast cancer survorl. The breast cancer survivors ususally have some physical diturbance that caused by the medication and also have psychological disorder cause by the removal of the breast. With the existence of interference issues of the breast cancer survivor, researchers made a psychological test to see the adjustment of a young adult women that is survive from the breast cancer. This test is called PDWSKP. For making PDWSKP researchers takes 31 respondents but only 18 respondets that can be used. This respondent was obtained through snowball sampling technique. In the preparation of PDWSKP, researchers used the theory of Huber and Runyon (1984) as a basis that consists of five domains. This 5 domain that had been made to be more contextual by putting in the result of interview with breast cancer survivors. The result of PDWSKP shows that from 25 items that have been tested by using reliability analysis all of the items are reliable (R= .880) but not externally valid when it is correlated with SWLS questionnare (r= -.129, p=609). From the calculation of corrected item total correlation, there are 4 items that’s not internally valid.